2018
DOI: 10.1371/journal.pone.0206717
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-cost analysis of the policy of mandatory annual rabies vaccination of domestic dogs in rabies-free Japan

Abstract: Japan is one of the few rabies-free countries/territories which implement the policy of mandatory vaccination of domestic dogs. In order to assess the economic efficiency of such policy in reducing the economic burden of a future canine rabies outbreak in Japan, a benefit-cost analysis (BCA) was performed using probabilistic decision tree modelling. Input data derived from simulation results of published mathematical model, field investigation conducted by the authors at prefectural governments, literature rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…With the strict quarantine policy, the risk of dog rabies introduction to Japan has been assessed to be very low (Kwan et al, 2017). The benefits for Japan to maintain mandatory dog rabies vaccination are high level of public and veterinary awareness of rabies prevention and a stable supply of animal rabies vaccines, but the cost is high (Kwan et al, 2018;Yamada et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With the strict quarantine policy, the risk of dog rabies introduction to Japan has been assessed to be very low (Kwan et al, 2017). The benefits for Japan to maintain mandatory dog rabies vaccination are high level of public and veterinary awareness of rabies prevention and a stable supply of animal rabies vaccines, but the cost is high (Kwan et al, 2018;Yamada et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study, whereas the data that we used are the estimation such as the dog population and the estimation of the number human infected, this impact should not be underestimated. A study in South Africa using highly dynamic population shown that 70% coverage rabies vaccination is effective to maintain critical threshold of rabies infection [13].…”
Section: Discussionmentioning
confidence: 99%
“…Even when a rabid dog enters Japan, it is unlikely to cause large outbreaks [247], partly because the probability for a dog to have contact with other dogs is low in Japan [248]. In that situation, the implementation of mandatory vaccination was shown to be economically inefficient [249,250].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%